What prevents midwifery quality care in Bangladesh? A focus group enquiry with midwifery students - Malin Bogren; Kerstin Erlandsson; Members of the Midwifery Faculty Master's degree holders in Sexual and Reproductive Health and Rights; Ulrika Byrskog (BMC, 2018)
Abstract Background With professional midwives being introduced in Bangladesh in 2013, the aim of this study was to describe midwifery students perceptions on midwives' realities in Bangladesh, based on their own experiences. Method Data were collected through 14 focus group discussions that included a total of 67 third-year diploma midwifery students at public nursing institutes/colleges in different parts of Bangladesh. Data were analyzed deductively using an analytical framework identifying social, professional and economical barriers to the provision of quality care by midwifery personnel. Results The social barriers preventing midwifery quality care falls outside the parameters of Bangladeshi cultural norms that have been shaped by beliefs associated with religion, society, and gender norms. This puts midwives in a vulnerable position due to cultural prejudice. Professional barriers include heavy workloads with a shortage of staff who were not utilized to their full capacity within the health system. The reason for this was a lack of recognition in the medical hierarchy, leaving midwives with low levels of autonomy. Economical barriers were reflected by lack of supplies and hospital beds, midwives earning only low and/or irregular salaries, a lack of opportunities for recreation, and personal insecurity related to lack of housing and transportation. Conclusion Without adequate support for midwives, to strengthen their self-confidence through education and through continuous professional and economic development, little can be achieved in terms of improving quality care of women during the period around early and late pregnancy including childbirth.The findings can be used for discussions aimed to mobilize a midwifery workforce across the continuum of care to deliver quality reproductive health care services. No matter how much adequate support is provided to midwives, to strengthen their self-confidence through education, continuous professional and economic development, addressing the social barriers is a prerequisite for provision of quality care.